Sestrin-2 is significantly increased in malignant pleural effusions due to lung cancer and is potentially secreted by pleural mesothelial cells. - Budanov, Andrei; Tsilioni, Irene; Flippidis, Aristotelis S.; Kerenidi, Theodora; Zarogiannis, Sotirios G.; Gourgoulianis, Konstantinos I. (My University, 2016)
Objectives: Sestrin-2 (Sesn2) belongs to a family of highly conserved antioxidant proteins that were discovered as p53-inducible proteins and inhibits cell growth and proliferation. Our aim was to assess the levels of Sesn2 in malignant pleural effusions of lung cancer patients compared to benign pleural effusions. Design and methods: We enrolled 73 patients (55/males and 18/females) diagnosed with pleural effusion (PE). PEs were grouped as 44malignant pleural effusions (MPEs; lung cancer) and 29 benign (BPE; 7 congestive heart failure, 9 tuberculosis, 13 parapneumonic). Pleural fluid (PF) Sesn2 levels were determined by enzymelinked immunosorbent assay (ELISA) kit. Standard biochemical PF analysis was also performed and Sesn2 levels were correlated with PF lactate dehydrogenase (LDH), protein, cell counts and age. Results: Sesn2 was detected in 24/44 patients with MPEs and in 3/29 patients with BPEs (p=0.0001). The mean value (mean ± SEM) of Sesn2 in patients with MPEs was 0.54 ± 0.22 ng/mL while in BPEs it was 0.12 ± 0.04 ng/mL (p =0.0004). In MPEs Sesn2 pleural fluid levels did not correlate with PF LDH and cell counts (p= 0.89 and p = 0.64 respectively). Conclusions: Our study shows that Sesn2 is significantly increased inMPEs compared to BPEs.Moreover, the lack of correlation of Sesn2 levels with PF cell counts and PF LDH suggests that it is potentially secreted by pleural mesothelial cells.
Keywords: Biomarkers; Sestrins; Sestrin-2; Lung cancer; Malignant pleural effusion; Pleural effusions; Ageing; Cancer; LUNG CANCER; Age-related disability; Health